Políticas públicas sobre drogas: uma avaliação narrada a partir de experiências juvenis na periferia de Fortaleza - Moreira, Bárbara Braz (2019)
The debate about psychoactive substances (SPA), commonly known as drugs, is increasingly present in public action. The State, as well as civil society, through public policies, think and develop actions of prevention, treatment and criminalization in the field of drugs, many of them distanced from the reality of the subjects, fruits of a project of moralistic and excluding class. Law 11.343 / 2006, of a prohibitionist nature, is the great mark today in Brazil to delineate political action, and is surrounded by contradictions and tensions. However, it is worth stressing that policies materialize in different ways in people's daily lives. Young people, who use SPA, residents of the periphery, in turn, have their daily lives crossed in a way differentiated by drug policy. However, it is questioned: in what form and to what extent these interventions are developed? How do these young people experience drug policy? This research proposes to evaluate the drug policy in Brazil through juvenile narratives, understanding how this policy interferes in the stories, trajectories, projects and dreams of these young people, since using drugs in Brazil is still a criminal act. Thus, I turn to qualitative, evaluative research to respond to such notes. I carry out an evaluation of drug policy, through Law 11.343 / 2006, from the perspective of juvenile experiences and narratives, which I call narrative evaluation, relating the text of the policy to the lived context. I also collaborate to strengthen a counter-hegemonic field for the evaluation of public policies, using a non-traditionalist evaluation, in order to break with the positivist and managerialist analyzes, most of which are related to the evaluation of public policies. To do so, I carry out a bibliographical research, reflecting on politics, State, evaluation, drug policies; documenting, accessing and analyzing the main legislations around this specific policy; (CUCA) where I talked to five young people, drug users, residents of the periphery, unstructured narrative interviews were conducted throughout 2017. As a result, the main indicators found were: 1) The democratic state as an exception in the periphery 2) Public security as central public policy in the daily life of the youth of the periphery through prohibitionist strategies, usurping rights.3) Experiences of unrest, terror and death common to the daily life of the interlocutors; 4- Possible care: centrality in the family, ignorance of the public spaces of treatment, CUCA as a powerful space to accommodate demands related to the use of drugs; 5- Urgent decriminalization of drug use as a matter of immediate survival.